2012
DOI: 10.1371/journal.pone.0049866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cold Pressor Stress on the Human Startle Response

Abstract: Both emotion and attention are known to influence the startle response. Stress influences emotion and attention, but the impact of stress on the human startle response remains unclear. We used an established physiological stressor, the Cold Pressor Test (CPT), to induce stress in a non-clinical human sample (24 student participants) in a within-subjects design. Autonomic (heart rate and skin conductance) and somatic (eye blink) responses to acoustic startle probes were measured during a pre-stress baseline, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 56 publications
3
19
0
1
Order By: Relevance
“…The CPT test was selected due to the efficient release of sympathetic neurotransmitters leading to marked vasoconstriction having an indirect effect in baroreflex mediating interactions [24][25][26] . Prior clinical and experimental studies have demonstrated significant cardiovascular responses to the cold stimuli, 27 . Specifically, the significant effect of CPT on left ventricular function has been demonstrated in a recent study 28 .…”
mentioning
confidence: 99%
“…The CPT test was selected due to the efficient release of sympathetic neurotransmitters leading to marked vasoconstriction having an indirect effect in baroreflex mediating interactions [24][25][26] . Prior clinical and experimental studies have demonstrated significant cardiovascular responses to the cold stimuli, 27 . Specifically, the significant effect of CPT on left ventricular function has been demonstrated in a recent study 28 .…”
mentioning
confidence: 99%
“…The alternative explanation relates to attentional mechanisms, and holds that the presence of pain or dyspnea draws attention inwards and as a consequence reduces responsivity to extraneous stimuli such as the auditory startle probe (Alius et al, 2015;Ceunen et al, 2013;Deuter et al, 2012;Pappens et al, 2010). If we would apply this explanation to our findings, then this would imply that esophageal pain did not reduce attention to extraneous stimuli in the women in our study, whereas it did in the men.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, when fearinducing dyspnea was elicited by CO 2 inhalation, it led to inhibition of startle, relative to startle measured during room air breathing (Pappens et al, 2012). Also during tonic cold pain and tonic heat pain, which are both interoceptive according to the definition of interoception forwarded by Craig (2002), no startle potentiation has been observed (Deuter et al, 2012;Horn et al, 2012). In contrast, during anxious anticipation of respiratory and other interoceptive sensations, the expected startle potentiation has been found (Hubbard et al, 4 | Startle responding in the context of visceral pain 4 2011; Lang et al, 2011;Melzig et al, 2008;Naliboff et al, 2009;Pappens et al, 2013;Twiss et al, 2009).…”
Section: Introductionmentioning
confidence: 77%
“…Before and after the CPT, participants were asked to evaluate their stress level on a 0-100% scale (0% -not stressed at all, 50% -moderately stressed, 100% -extremely stressed). Studies show that CPT activates the sympathetic nervous system (Deuter et al, 2012). We assume that CPT (as a tool to provoke acute physiological stress) has an impact on changes in participants' hearth rate variability (HRV).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the CPT elicits sympathetic nervous system activity (Deuter et al, 2012) and excitates physiological stress. Results of our study shows a decrease in residents HRV after the CPT which means that resources of the autonomic nervous system were utilized in order to cope with induced physiological stress.…”
Section: Studymentioning
confidence: 99%